PENGARUH PENGGUNAAN POCKET BOOK SISWA DENGAN TEKNIK EVALUASI MEDIA PUZZLE CERIA TERHADAP AKTIVITAS DAN HASIL BELAJAR - Mukminah Mukminah; Bq Azmi Sukroyanti; Muhammad Fuaddunazmi (Lensa: Jurnal Kependidikan Fisika, 2015)
Thie aims of this research was to measure the influence of student pocket book usage by using evaluation technique on cheerful puzzle media towards activity and the learning outcomes of physic, on vibration and wave. The research implied on Quasi Experiment with the design of Pretest-Posttest Control Group Design. The research sample taken by purposive sampling technique. The research instrument used on the collecting data process is observation sheet and multiple choice test. Based on the average of student activity on the experiment class was higher than class control. Based on the data, on the experiment class found that the average of the first meeting was 73,33%, and on the second meeting was found that 81,33%. Which categorized as very good and excellent, meanwhile on the control class for the first meeting was found the average of student activity was 64% and the second meeting shown that 57,3% which categorized enough and good enough. The average of the result of study on experiment class was 52,5 and for the class control was 53,8. In tears of posttest data resulted, the average of experiment class was 70,67, and the control class was 65,17. Based on the result of t-test data, posttest resulted tcalculate > ttable (14,05>2,03) with  = 5%, and found that alternative hypothesis (Ha) accepted. Thus it can be conclude that there is influence of using pocket book for student with the evaluation technique on cheerful puzzle media towards activity and learning outcomes study on the topic vibration and wave at  SMP 11 Mataram.